Unraveling the Pathways to Teacher Performance: The Mediating Role of Job Satisfaction and Commitment - Muhaidir Ikram. M; Ade Vidya Eryanti; Andi Nurfiana Haz (Sean Institute, 2025)
Indonesia is currently facing challenges related to the quality of education, reflected in the low performance quality achieved by teaching staff. This phenomenon is also evident at Madrasah Aliyah in Gowa Regency, where teacher performance is sub-optimal and teacher competence scores are low. This study aims to analyze and understand the influence of Transformational Leadership and Teacher Competence on Teacher Performance in Madrasah Aliyah (Islamic Senior High Schools) in Gowa Regency, by examining the mediating roles of Job Satisfaction and Organizational Commitment.This quantitative research employed a data collection method utilizing questionnaires distributed to 132 teaching staff and was analyzed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) technique. The results consistently demonstrate that both Transformational Leadership and Teacher Competence exert a positive and significant influence on Teacher Performance, both directly and indirectly through mediation. It was found that Job Satisfaction and Organizational Commitment significantly function as partial mediating variables across all relationship pathways. The strongest indirect effect was observed in the path from Teacher Competence to Teacher Performance as mediated by Organizational Commitment, suggesting that optimal strengthening of teacher competence primarily drives performance through an increased loyalty and emotional attachment to the Madrasah. Overall, this study affirms that Teacher Performance in Madrasah Aliyah in Gowa Regency is highly dependent on the reinforcement of Competence, supported by effective Transformational Leadership, and maintained through high Job Satisfaction and Organizational Commitment.